Design of Student Attendance Information System at MTS Assalafiyah, Tegal City - Silvia Berliana Ghany; Muhammad Fadlullah (Yayasan Kita Menulis, 2025)
The Attendance Information System is a modern solution for recording student attendance in schools, replacing conventional manual attendance lists. Student attendance tracking comprises two main aspects: attendance timekeeping and working timekeeping. With technological advancements, particularly in computing, educational institutions can leverage these tools to enhance operational efficiency. This study aims to design and develop a web-based Student Attendance Information System at MTs Assalafiyah Kota Tegal. The system is designed to streamline attendance management, making it faster, more structured, and resource-efficient. The research employs the waterfall development method, consisting of several stages: requirements analysis, system design, coding, testing, and implementation for end-users. These stages are carried out sequentially to ensure that the system meets the needs of all stakeholders, including students, teachers, and school administrators. Using a web-based system supported by online networks, attendance processes can be conducted in real-time and with greater transparency. The results of this study are expected to significantly contribute to administrative efficiency in schools, improve the accuracy of student attendance data, and simplify the management of attendance records in educational settings. Additionally, this system supports digitalization efforts in education, particularly in school administration.